Stand alone : how to be an extraordinary leader - Lloyd, Sabrina (Ascent Audio, 2023)
So many people are telling you what you want to hear. Finally someone is saying what we all need to hear. The truth about success is breathtaking and needed now more than ever. This book demonstrates what it really takes to succeed. Learn how to overcome obstacles and create the life you want by becoming the leader you were meant to be. Stand Alone will help you see how you can go from living an ordinary life-where life just happens to you-to living a life of significance and influence.